2006
DOI: 10.1016/j.aquaculture.2005.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Changes in metabolic and immunological variables of wild and pond-reared southern white shrimp Litopenaeus schmitti adult males during continuous reproductive activity

Abstract: Reproductive performance of male southern white shrimp Litopenaeus schmitti decreased over time possibly attaining a reproductive exhaustion that results in a lower physiological condition that includes a decreased immune response capacity. Several indicators of immune and metabolic status such as phenoloxidase activity (PO), total hemocytes count (THC), hemoagglutinating activity (HA), total proteins, and glucose concentration in the hemolymph were analyzed in wild and pond-reared adult males at 3, 30, and 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…Such artificially induced PO activity in the EDTA-containing plasma obviously does not represent the actual PO activity of the organism, but has also been used in recent studies [9,13]. Therefore, it is suggested that PO activity reported in previous studies [4,5,9,13] should be reconsidered.…”
Section: Effects Of Reaction Conditionsmentioning
confidence: 89%
See 4 more Smart Citations
“…Such artificially induced PO activity in the EDTA-containing plasma obviously does not represent the actual PO activity of the organism, but has also been used in recent studies [9,13]. Therefore, it is suggested that PO activity reported in previous studies [4,5,9,13] should be reconsidered.…”
Section: Effects Of Reaction Conditionsmentioning
confidence: 89%
“…Although the inhibition effect of EDTA on PO activity has been reported in previous studies [12], EDTA-containing anticoagulant has still been used to separate plasma for PO activity assay in recent studies [4,5,9,13]. In this study, PO activity (35.36 AE 4.53 U ml À1 hemolymph) in the sample prepared with EDTA-containing anticoagulant, is only 6% of that in the EDTA-free sample (604.56 AE 53.12 U ml À1 hemolymph), and independent t-tests indicate that PO activity is significantly inhibited by EDTA (P < 0.05) ( Table 1).…”
Section: Effects Of Reaction Conditionsmentioning
confidence: 98%
See 3 more Smart Citations